Phonon Confinement Effect on Lattice Thermal Conductivity of Zn4Sb3 Quantum Well Structure - Jubayr, M. R. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
We have theoretically investigated the in-plane lattice thermal conductivity of Zn4Sb3single quantum well structure taking into account spatial confinement of phonons. The calculations were carried out for free-surface quantum wells with thickness 8.5nm in the room temperature. We show that the lattice thermal conductivity is a significant reduce. The reduction is mostly due to the drop in the average group velocity caused by the spatial confinement of acoustic phonons and the corresponding increase in phonon relaxation rates. The predicted decrease is important for the anticipated applications of Zn4Sb3 nanostructure materials for room-temperature thermoelectric devices. Our theoretical results are in a good agreement with available experimental data for Zn4Sb3 quantum wells